الضغوط النفسية على وفق بعض المتغيرات الديموغرافية لدى موظفي الجامعة - الوائلي، تحرير زكي (جامعة ميسان - كلية التربية, 2018)
يعيش العديد من موظفي دوائر ومؤسسات الدولة تحت تأثير الضغوط النفسية الناجمة عن الالتزامات الحياتية وأعباء العمل الإضافية، التي تنعكس سلبا على إنتاجيتهم وسوء تكيفهم في بيئة العمل. وتأتي الأهمية النظرية لهذا البحث من أهمية دراسة الضغوط النفسية (STRESS) بوصفها موضوعا ذات تأثير واضح في حياة الأفراد وسلامتهم النفسية. إذ يعد الموظفون بشكل عام من الشرائح الاجتماعية المهمة، كما هم موظفو الجامعة لما لهم من دور فاعل في تسير العملية التعليمة بوصفهم السند القوي والركن المتين للتدريسي الجامعي في تحقق نجاح العمل الجامعي. وتتجلى أهمية البحث التطبيقية بوصفه قد يسهم في رصد الجوانب السلبية في السلوك العام لموظفي الجامعة من خلال تحديد مؤشرات الضغوط النفسية لديهم. واستهدف هذا البحث التعرف إلى ما يأتي: 1. الضغوط النفسية لدى موظفي الجامعة. 2. الفرق في الضغوط النفسية لدى موظفي الجامعة على وفق المتغيرات الديموغرافية الآتية: (أ) النوع (ذكور، إناث). (ب) الحالة الزوجية (متزوج -أعزب). واشتملت عينة البحث على (100) موظف وموظفة. وتبنت الباحثة مقياس الضغوط النفسية من إعداد (العنزي، 2014). وبينت نتائج البحث أن جميع أفراد عينة التطبيق النهائي للبحث وبنسبة (100%) لديهم مؤشرات الضغط النفسية. وهناك علاقة بين الضغوط النفسية والمتغيرات الديموغرافية المحددة في هذا البحث. وقدمت الباحثة في نهاية البحث مجموعة من التوصيات والمقترحات. Many employees of state departments and institutions live under the influence of psychological stress resulting from life commitments and additional workloads, which negatively affect their productivity and maladaptation in the work environment. The theoretical importance of this research comes from the importance of studying stress as a subject with a clear impact on the lives and psychological well-being of individuals. In general, staff are important social strata, as are university staff, because they have an active role to play in the teaching process as the strong bond and solid foundation of university education in achieving the success of university work. The importance of applied research as it may contribute to monitoring the negative aspects in the general behavior of university staff by identifying indicators of psychological stress. This research aimed to identify the following: 1. Psychological pressure of university staff. 2. The difference in psychological stress among university staff according to the following demographic variables: (A) Gender (male, female). (B) Marital status (married - single). The research sample included (100) employees and employees. The researcher adopted the psychological stress gauge by Al-Enezi (2014). The results of the study showed that all members of the sample of the final application of the research and (100%) have indicators of psychological pressure. There is a relationship between psychological stress and the demographic variables identified in this study. Recommended and suggested by the researcher according to the results of the research.
Keywords: العمل الأكاديمي -- المشكلات التنظيمية -- علاقات العمل -- الأزمات النفسية -- الرضا الوظيفي